Segmental fat‐free and fat mass measurements by bioelectrical impedance analysis in 2, 224 healthy spanish women aged 18–85 years. Issue 4 (29th November 2014) - Pedrera‐Zamorano, Juan D.; Roncero‐Martin, Raul; Lavado‐Garcia, Jesus M.; Calderon‐Garcia, Julian F.; Rey‐Sanchez, Purificacion; Vera, Vicente; Martinez, Mariana; Moran, Jose M.
Abstract Objectives This study provides updated data on body composition in adult Spanish women. Methods We considered data, including height and weight, from a survey conducted on a total of 4, 013 adult women between 2009 and 2010. A subgroup of 2, 224 women completed a bioelectrical body impedance analysis of body composition using a Tanita Body Composition Analyzer (Model no. BF‐418). Results Total fat mass (FM) gradually increased between 18 and 74 years of age and decreased thereafter. FM increased in both legs between 65 and 74 years of age (5.69 ± 1.4 Kg and 5.66 ± 1.4 Kg for right and left legs, respectively) and decreased thereafter. FM in the right arm increased until 44 years of age (1.22 ± 2.6 Kg), decreased to 1.19 ± 0.5 Kg between 45 and 54 years of age, and increased to 1.54 ± 0.63 from 65 to 74 years of age. FM in the left arm increased constantly until it reached a peak of 1.63 ± 0.6 Kg between 65 and 74 years of age and decreased thereafter. FM increased in the trunk throughout life (peaks at 13.27±3.8 Kg) until subjects reached between 65 and 74 years of age. Fat free mass increased until 44 years of age (42.42 ± 4.17 Kg) and decreased thereafter. The prevalence of overweight/obesity significantly increased with age in the entire sample. Conclusions Our results indicate that age‐related increases in weight were at least partially due to increased adiposity. Am. J. Hum. Biol. 27:468–474, 2015. © 2015 Wiley Periodicals, Inc.